Nondestructive extraction DNA method from bones or teeth, true or false?. (December 2015) - Gomes, C.; Palomo-Díez, S.; Roig, J.; López-Parra, A.M.; Baeza-Richer, C.; Esparza-Arroyo, A.; Gibaja, J.; Arroyo-Pardo, E.
Abstract: One of the most challenging points for ancient DNA studies on human remains is that analysing procedures involve partial or total destruction of the samples, which usually are unique and irreplaceable. This is what prevents museums, anthropologists or archaeologists from giving samples for genetic investigation. So that it is interesting to find an analysing method without destroying them. In this study, it was carried out the evaluation of a non-destructive extraction DNA protocol on 4 Neolithic individuals, from Can Gambús (Sabadell, Spain) and 4 pre Bell Beaker period individuals, from Los Cercados (Valladolid, Spain). Along this work, it was discussed the efficiency of the non-destructive protocol, valuing the obtained result, and the evidences state of preservation after the whole procedure.